2022
DOI: 10.1186/s13046-022-02337-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to immune checkpoint inhibitor dictated by pre-existing differential immune profiles in squamous cell carcinomas caused by same initial oncogenic drivers

Abstract: Background While immune checkpoint inhibitors (ICI) were approved for head and neck squamous cell carcinomas (HNSCCs), the response rate remains relatively low. Mechanisms underlying ICI unresponsiveness versus sensitivity are not fully understood. Method To better delineate differential responses to ICI treatment, we employed mouse SCC models, termed KPPA tumors that were caused by deleting p53 and hyperactivating PIK3CA, two most frequently mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 108 publications
(82 reference statements)
1
21
0
Order By: Relevance
“…We employed conventional flow cytometry and single-cell RNAsequencing to identify the difference in TILs. We found that TAb2 and TCh3 KPPA tumors exhibited heterogeneous immune profiles pre-existing treatment that dictated their unresponsiveness or sensitivity to anti-PD-L1 (18). Others have established murine HNSCC cell lines from primary 4NQO-induced tumors in the tongue of C57BL/6 (B6) mice, which were designated 4MOSC, short for 4NQO-induced murine oral squamous cells (65).…”
Section: Differential Responses To Ici In Mouse Hnscc Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…We employed conventional flow cytometry and single-cell RNAsequencing to identify the difference in TILs. We found that TAb2 and TCh3 KPPA tumors exhibited heterogeneous immune profiles pre-existing treatment that dictated their unresponsiveness or sensitivity to anti-PD-L1 (18). Others have established murine HNSCC cell lines from primary 4NQO-induced tumors in the tongue of C57BL/6 (B6) mice, which were designated 4MOSC, short for 4NQO-induced murine oral squamous cells (65).…”
Section: Differential Responses To Ici In Mouse Hnscc Modelsmentioning
confidence: 96%
“…We recently established a genetically engineered mouse model by deleting p53 and constitutively activating PIK3CA in mouse keratin 15-expressing (K15 + ) stem cells, which leads to the spontaneous development of multi-lineage tumors including SCCs, termed keratin-15-p53-PIK3CA (KPPA) tumors ( 14 ). Furthermore, we derived transplantable daughter cell lines from KPPA tumors, which may provide a platform for testing new therapeutic strategies in HNSCCs ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…TAMs’ role as major carriers of checkpoint inhibitor ligands (e.g., PDL-1/2, B7-H4, VISTA) and as mediators of T-cell exhaustion has been well described [ 181 ]. Studies have also revealed how an increased concentration of M2-polarized TAMs mediate anti-PD-L1 ICI resistance in HNSCC and in prostate cancer [ 182 , 183 ].…”
Section: Basic Research In Cancer Immunologymentioning
confidence: 99%
“…Therefore, immune evasion was added to the list of hallmarks of cancer in 2010 [5]. Although some of the mechanisms of immune evasion can be related to direct interactions between malignant cells and the immune effectors, there are numerous instances when TME serves for cancer as a protector against the immune system and/or immunotherapies [6][7][8].…”
Section: The Role Of Tme In Tumor Immune Evasionmentioning
confidence: 99%